1980
DOI: 10.1097/00004032-198004000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Uranium Content in Dental Porcelains by Means of the Fission Track Method and Estimation of Radiation Dose to Oral Mucosa by Radioactive Elements

Abstract: Porcelain teeth, some of which contain uranium compounds for aesthetic purpose, have been widely used in dental clinics. Hazardous effects due to uranium radiation have been suggested in recent publications.In the present study, the authors carried out the determination of uranium concentrations in four major brands of porcelain teeth marketed in Japan using the fission track method, and the absorbed doses to oral tissues were calculated by a formula introduced by the authors for calculation of alpha radiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

1985
1985
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 1 publication
0
5
1
Order By: Relevance
“…The measured values for uranium and thorium were below the levels found in previous works, ranging from few tenths of Bq kg À1 up to several thousands of Bq kg À1 (Papastefanou et al, 1987;Sairenji et al, 1980), dating back to the period when addition of uranium to dental porcelain materials was still permitted. The specific activities of 40 K were in good agreement with the earlier determinations.…”
Section: Discussioncontrasting
confidence: 67%
See 3 more Smart Citations
“…The measured values for uranium and thorium were below the levels found in previous works, ranging from few tenths of Bq kg À1 up to several thousands of Bq kg À1 (Papastefanou et al, 1987;Sairenji et al, 1980), dating back to the period when addition of uranium to dental porcelain materials was still permitted. The specific activities of 40 K were in good agreement with the earlier determinations.…”
Section: Discussioncontrasting
confidence: 67%
“…Already Sairenji et al (1980) had pointed out that the beta dose to oral mucosa due to 40 K was about the same order of magnitude as the dose due to beta particles emitted by the radionuclides of the U/Th chains (mainly by 234m Pa) in porcelains containing 50e200 ppm U (about 600e2500 Bq kg À1 ), and that alpha contribution to the dose was negligible. Their calculation had indeed shown that already at depths greater than 20 mm the main contribution to the dose was due to the beta particles, since the emitted alpha particles have maximum ranges in tissue of less than 30 mm, and they may additionally be absorbed already in the layers of saliva and/or dental plaque deposited on the surface of teeth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to mimic the optical properties of living natural teeth, natural radioactive elements such as uranium and natural or depleted uranium salts were added into porcelain powder, used in the construction of artificial porcelain dental crowns-bridges prosthesis [2][3][4]. Used in dentistry the concentration of uranium in porcelain teeth and porcelain powder and the dose rate absorbed by the oral mucosa has been investigated in several studies [5][6][7][8][9]. In a study conducted in Sweden prosthesis porcelain teeth in different brands available on the market in amounts ranging from 15 to 186 ppm uranium content was determined [10] and stopping the use of dental ceramics containing over 100 ppm uranium were requested [2].…”
Section: Introductionmentioning
confidence: 99%